Electron-Rich Amino Heterocycles for Regiospecific Synthesis of Trifluoromethyl-Containing Fused Pyridines - Volochnyuk, Dmitriy; Pushechnikov, Alexei; Krotko, Dmitriy; Sibgatulin, Dmitriy; Kovaleva, Svetlana; Tolmachev, Andrei (My University, 2003)
The reaction of 4,4,4-trifluoro-3-oxobutanoates with the corresponding electron-rich amino heterocycles was investigated. A simple and flexible general procedure for the regiospecific annulation of the trifluoromethylpyridine ring to electron-rich amino heterocycles was proposed. A set of CF3-containing fused pyridines in almost quantitative yield was obtained.
Keywords: фтор; електрофільне заміщення; анелювання; гетероцикли; піридин; electrophilic substitution; annulations, heterocycles; pyridines; fluorine; кафедра харчової хімії